1984
DOI: 10.1177/014272378400501503
|View full text |Cite
|
Sign up to set email alerts
|

Young children's coordination of gestural and linguistic reference

Abstract: The current study investigated the relationship between young children's linguistic and nonlinguistic communicative strategies. Twenty-three children, 20-44 months of age, served as subjects. In a naturalistic setting, an adult gave signs of noncomprehension (a contingent query) to each of the child's object references. The child's original linguistic reference and use of gestures were recorded and compared to his/her subsequent linguistic and gestural responses to the adult query. Results showed that the chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 8 publications
3
10
0
Order By: Relevance
“…O'Neill & Topolovec, 2001 ;Tomasello, Anselmi & Farrar, 1985 ;Wilcox & Howse, 1982). Our non-linguistic pragmatic hypothesis that a non-linguistic pragmatic strategy is used when non-lexical forms are used in reference to new information was supported with respect to the English-speaking children and mothers.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…O'Neill & Topolovec, 2001 ;Tomasello, Anselmi & Farrar, 1985 ;Wilcox & Howse, 1982). Our non-linguistic pragmatic hypothesis that a non-linguistic pragmatic strategy is used when non-lexical forms are used in reference to new information was supported with respect to the English-speaking children and mothers.…”
Section: Discussionmentioning
confidence: 58%
“…It is possible that both the Japanese-speaking mothers and children might have omitted new arguments when they represented referents that were present in the situational context and were accompanied by deictic gestures, such as pointing or touching to indicate intended referents in discourse. A study by Tomasello, Anselmi & Farrar (1985) with English-speaking children (ranging in age from 1 ;8 to 3;8) showed that the children tended to use gestures more often when using a pronominal form than when using a lexical form in response to an adult's query for clarification, indicating that they were sensitive to the lower specificity and informational value of pronominal arguments. If a lexical form is not used, then an alternate referential strategy would need to be employed, such as the use of a non-linguistic pragmatic strategy, in order for the speaker to adequately point out the new referent to the listener.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above‐reviewed studies have focused on children aged 4 and older, so we do not know whether 2‐year‐olds, for example, would also benefit from feedback. There is now ample evidence that children repair their failed communicative attempts even at the preverbal stage (Golinkoff, 1986, 1993; Liszkowski, Carpenter, & Tomasello, in press; Tomasello, Carpenter, & Liszkowski, in press) and often respond to clarification requests in an appropriate manner by the age of 2 (Anselmi, Tomasello, & Acunzo, 1986; Gallagher, 1977; Tomasello, Anselmi, & Farrar, 1984/1985). However, it is not clear that children this young are able to infer from the fact that someone has asked for clarification that their original attempt at reference was not sufficiently informative (as opposed, e.g., to not being heard).…”
mentioning
confidence: 99%
“…Elicitation tests are notoriously difficult to conduct with children this young but Garton's well-chosen methodology enables her to show that while at three years children certainly do produce these terms, knowledge of their contrastive functions is still developing. Other recent work (Tomasello, Anselmi & Farrar 1984/1985 has shown that by the third year children are aware of important relationships between gestures and language, and are sensitive to the lack of specificity of pronouns. Garton illustrates some of the implications of the integration of gesture and language for the early use of deictic terms, and she discusses this with attention to semantic, pragmatic and cognitive factors bearing on spatial reference in the preschooler.…”
Section: Editorial Introductionmentioning
confidence: 97%